The Impact of Social Phenomena on the Study of Religion: A Case Study of Sharar’s Masīḥ aur Masīhiyat - Ibrahim Shoukat; Dr. Muhammad Qasim (MEI, 2025)
This research paper explores how social conditions can shape the way religious stories are told, using Abdul Haleem Sharar’s Masīḥ aur Masīḥīyat as a case study. Sharar, a prominent Urdu writer in colonial India, narrates the story of Jesus not only to describe the origins of Christianity but also to reflect on the social challenges faced by Indian Muslims under British rule. Through his storytelling, Sharar depicts a fractured Jewish society under Roman control, divided, spiritually weakened, and socially oppressed, and then introduces Jesus as a moral reformer who calls people back to truth, justice, unity, and social renewal. This message subtly mirrors the struggles of Muslims in Sharar’s own time. The paper looks at how Sharar blends history, literature, and moral advice to speak to his readers without directly criticizing them. By presenting Jesus as a model of spiritual strength and honest leadership, Sharar offers a message of hope and renewal for a community that had lost its direction. He doesn’t debate theology or attack other faiths. Instead, he uses a respectful and emotional tone to make the story real and socially relevant. This approach allowed him to share strong ideas safely in a colonial context, where open criticism could lead to trouble. Overall, the study shows that Masīḥ aur Masīḥīyat is more than just a book about Christian history; it is a thoughtful response to the social crisis of the time. Sharar’s work shows how religion can become a mirror for self-reflection and a guide for community and social reform when told through the right lens. His message remains relevant today as an example of how literature and faith can be used to understand and respond to social change.